Publishing the Grail in medieval and Renaissance France - Tether, Leah ca. 20./21. Jh (Boydell & Brewer, 2017)
The Grail is one of the most enduring literary motifs in publishing history. In spite of an ever-changing world, the reading public has maintained a fascination for this enigmatic object, as well as the various adventures and characters associated with it. But the nature and reception of the Grail have not remained static. Thanks to the fact that the first known author of a Grail story, Chrétien de Troyes, died c.1180-90 before completing his tale and revealing the meaning of the Grail, authors and publishers across history have reimagined, reinterpreted and re-packaged Grail literature so as to appeal to the developing tastes and interests of their target audiences. This book analyses the developing publication practices associated with French Grail literature in medieval and Renaissance France. Arguing for pre-print book production as constituting an early incarnation of a publishing trade, it discusses such matters as the disclosure of authorship and patronage, and the writing and formatting of blurbs, as well as tactics of compilation as production techniques that bear evidence of common commercial motivations between pre- and post-print publication. The distinctive investigation of manuscript and early-print evidence brings medieval and early-modern publishers and their concepts of both product and market into focus. Leah Tether is Reader in Medieval Literature and Digital Cultures, and Co-Director of the Centre for Medieval Studies at the University of Bristol. She is the author of The Continuations of Chrétien's Perceval: Content and Construction, Extension and Ending (D.S. Brewer, 2012)
Title from publisher's bibliographic system (viewed on 08 Jun 2018)
Keywords: Geschichte 1180-1530; Grail / Legends / History and criticism; French literature / To 1500 / History and criticism; rench literature / 16th century / History and criticism; Edition; Artusepik; Frankreich